Activated carbon from cassava peel: a promising electrode material for supercapacitors (2019)
Supercapacitors are conventional devices in electrical circuits that produce electrical pulses at high power levels in short periods. Electrodes for supercapacitors were prepared with activated carbon. Activated carbon was obtained from cassava peels treated by chemical activation with potassium hydroxide (KOH) and phosphoric acid (H3PO4), each at two different concentrations and at one carbonization temperature. The electrochemical performance of the prepared electrodes was obtained by means of cyclic voltammetry and galvanostatic charge-discharge in a 3-electrode system with an electrolytic solution of sulfuric acid (H2SO4) 1 M. Cyclic voltammetry allowed identifying the behavior of supercapacitors in a potential window of -0.4V to 0.6V. Activated carbon derived from cassava peel with the highest specific surface area (398.46 m2 /g) has exhibited the maximum specific capacitance of 64.18 F/g.